Isocyanate deoxygenation by a molecular magnesium silanide. Issue 1 (6th December 2021) - Okokhere-Edeghoghon, Bibian; Neale, Samuel E.; Hill, Michael S.; Mahon, Mary F.; McMullin, Claire L.
Abstract : A molecular magnesium silanide is shown through a combined synthetic and computational study to effect siloxide formation and isocyanate deoxgenation via the initial formation of magnesium silamidate intermediates. Abstract : The stoichiometric reactivity of a β-diketiminato (BDI) magnesium silanide towards a variety of organic isocyanates has been assessed. While the primary outcome of reactions of t -BuNCO, DippNCO and CyNCO was the production of β-diketiminato magnesium siloxide adducts of the isonitrile resulting from isocyanate deoxygenation, analogous treatment with i -PrNCO led to multiple products, four of which have been positively identified. Although the specificity of this latter reaction was hampered by competitive isocycanate addition at the γ-methine carbon of the BDI supporting ligand, the identification of [{ i -PrNCO}CH{(Me)CNDipp}MgMe2 PhSiC(O)N i -Pr]6 provided corroborative evidence for the likely generation of sila-amidate intermediates in all four reactions under study. The formation of [Me2 PhSiC(O)NR] − anions as the most likely initial species formed en route to isonitrile and siloxide formation was, therefore, validated by a computational density functional theory (DFT) study.